Hubungan Status Hipertiroid dengan Tingkat Depresi Usia Dewasa Tengah di Komunitas Pita Tosca Wilayah DKI Jakarta: The Relationship Between Hyperthyroid Status and the Level of Depression in Middle-Aged Adults in the Pita Tosca Community in the DKI Jakarta Area - Rotua Dinarta Sihombing; Sancka Stella; Lannasari (Journal of Nursing Education and Practice, 2021)
Introduction: Depression is a mental disorder in which a person exhibits symptoms of a gloomy demeanor, persistent sadness, and a sense of being overwhelmed. Hyperthyroidism is one of the conditions in which the thyroid gland produces an excessive amount of thyroid hormones, leading to increased metabolism in peripheral tissues. Objective: This study aims to determine the relationship between hyperthyroidism status and the level of depression in middle-aged adults. Method: This research is a correlational study that identifies the relationship between the occurrence of hyperthyroidism and the occurrence of depression in the Pita Tosca community in the DKI Jakarta area. Result: The results of this study indicate that all respondents with hyperthyroidism were female, accounting for 97.3% of the sample. Marital status and employment status showed no statistical relationship to the occurrence of hyperthyroidism. Nearly half of the respondents with above-normal thyroid levels (hyperthyroidism) experienced moderate depression, with a percentage of 40.5%. Conclusion: From this study, it can be concluded that there is a relationship between hyperthyroidism status and the level of depression in middle-aged adults in the Pita Tosca community in the DKI Jakarta region in 2021, with a p-value of 0.030.